ANALISIS PENGARUH PROMOSI MEDIA SOSIAL TERHADAP MINAT KUNJUNGAN ULANG MELALUI KEPUASAN PASIEN PADA RSUD LAMADDUKELLENG SENGKANG - Agus Purwanto (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2026)
The goal of this study is to determine how patient satisfaction and Instagram advertising influence a patient's desire to return for treatment. The analytical approach used in this study is path analysis, which is quantitative. The sample was chosen using a purposive sampling technique, which yielded 80 participants out of a total patient population of 450. A survey instrument that had been tested for validity and reliability was used to gather the data. Path analysis with simple and multiple regression, along with the Sobel test, were among the data analysis approaches used. The study's findings demonstrate that: (1) The path coefficient for the influence of Instagram promotion on patient satisfaction is 0. 158, with a significance level of 0. 161 < 0. 05; (2) The path coefficient for the influence of Instagram promotion on patient revisit intention is 0. 052, with a significance level of 0. 615; (3) The path coefficient for the influence of patient satisfaction on revisit intention is 0. 443, with a significance level of 0. 000; (4) The indirect effect of Instagram promotion on patient revisit intention through patient satisfaction is 5. 20%, with an indirect effect of 6. 99% and a p-value of 0. 633 based on the Sobel test. The findings of this study are as follows: (1) Instagram promotion has no discernible impact on patient satisfaction; (2) Instagram promotion has no discernible impact on patient revisit intention; (3) patient satisfaction has a positive and significant effect on patient revisit intention; and (4) Instagram promotion does not indirectly influence patient revisit intention through patient satisfaction.